PERAN PENDIDIKAN AGAMA ISLAM DALAM MENJAGA PENDIDIKAN TOLERANSI BERAGAMA DI KELUARGA - Yudi Hariansyah; Kusen Kusen; Hadi Suhermanto (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
Religious tolerance is an urgent problem faced by the Indonesian nation. The main problem in this article is how Islamic religious education maintains religious tolerance education in the family in Suro Bali village, Ujan Mas sub-district, Kepahiang district, Bengkulu province. This study used a qualitative method, the aim of the study was to find Islamic religious education efforts in maintaining religious tolerance education in the family. The results of this study emphasize that the family plays an important role in instilling tolerance education in religion in an effort to maintain unity and harmony in communities of different religions. The implementation of tolerance education in interfaith communities in Suro Bali Village, Kepahiang Regency usually uses educational methods in the family which include methods of advice, exemplary methods, habituation methods, training methods and methods of punishment. All of these methods include several values of tolerance education that have been implemented in an effort to maintain religious tolerance education in families in interfaith communities.